Rattling the Cage: Incarcerated Men, Gender and the Construction of Maleness - Irene C. Baird (Adult Education Research Conference, 2004)
This excerpt from Vanzant speaks to the purpose of this research with incarcerated males. Succinctly, the issue—Vanzant's "harmful actions"/male criminal activity—is an age-old one with punishment as the antidote. This study, alternatively, chose to look at the issue from a learning perspective: men's learning, outside of the academy, to gain insights into themselves, their being as men, and to take ownership for "rerighting" themselves (their words), with literature serving as the medium.